2016
DOI: 10.1093/gerona/glw237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calorie Restriction in Obese Older Adults: The CROSSROADS Randomized Controlled Trial

Abstract: While moderate calorie restriction did not significantly decrease VAT in older adults at high risk for cardiometabolic disease, it did reduce total body fat and cardiometabolic risk factors without significantly more adverse events and lean mass loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 33 publications
1
42
1
2
Order By: Relevance
“…In this study, we observed that SG decreased COMT as well as renin and Ang-II levels in the kidney compared with PF. There are conflicting observations, given that caloric restriction is a first-line therapy recommendation for individuals with obesity and that several clinical studies have shown specific renal benefits of caloric restriction on BP, proteinuria, and renal function (39,40). However, these findings are not necessarily contradictory to our results.…”
Section: Discussioncontrasting
confidence: 90%
“…In this study, we observed that SG decreased COMT as well as renin and Ang-II levels in the kidney compared with PF. There are conflicting observations, given that caloric restriction is a first-line therapy recommendation for individuals with obesity and that several clinical studies have shown specific renal benefits of caloric restriction on BP, proteinuria, and renal function (39,40). However, these findings are not necessarily contradictory to our results.…”
Section: Discussioncontrasting
confidence: 90%
“…VLEDs were associated with constipation, dizziness, cold intolerance (all of which are well documented), and minor increases in urea and creatinine . Where adverse events were reported, these were related to falls during exercise interventions . Large weight loss studies, which followed up participants for 7 and 9 years, found no increase in mortality in those randomized to the weight loss arm compared with those who were not.…”
Section: Resultsmentioning
confidence: 97%
“…No adverse effects were observed. In conclusion, it was found that, although it did not reduce the visceral fat content, moderate calorie restriction decreased the total fat content and cardiometabolic risk [34]. A study by Bell et al on 6.940 people aged from 50 to 90 (National Alzheimer's Coordinating Center Uniform Data Set) showed that rapid weight loss (> 5% in 12 months) during 3.8 years of observation resulted in increased mild cognitive impairment and dementia, while a low (but stable) weight was not associated with an increased risk of these disorders.…”
Section: Redukcja Masy Ciała Jako Zalecenie Leczniczementioning
confidence: 83%
“…Efekty planowych modyfikacji dietetycznych (w zakresie podaży kalorii) u otyłych starszych przedstawia Ard i wsp. [34]. Obserwacja trwała 52 tygodnie i obejmowała 164 starszych otyłych, których podzielono na grupy.…”
Section: Redukcja Masy Ciała Jako Zalecenie Leczniczeunclassified